Anti-Diabetic and Antioxidant Effect Evaluation of Thai Shallot and Cha-Miang in Diabetic Rats - Jiraporn Laoung-on; Artorn Anuduang; Chalermpong Saenjum; Kittipan Rerkasem; Somdet Srichairatanakool; Kongsak Boonyapranai; Sakaewan Ounjaijean (Biology)
Background: Type 2 diabetes mellitus is a chronic metabolic disease related to obesity and high-calorie diets, which presents hyperglycemia and insulin resistance. The management of diabetes can cause a rise in financial burden and synthetic medications can have adverse effects. This study aims to investigate the anti-diabetic and antioxidant activity of SHE, CME, and SHE in diabetic rats. Methods: Seventy-eight rats were randomly assigned to the following 13 groups (n = 6): N-DW, D-DW, D-M, D-S, D-C, D-F, D-SC, D-SF, D-SM, D-CM, D-FM, D-SCM, and D-SFM, for 8 weeks. Body weight, relative organ weight, blood glucose, insulin resistance, and plasma biomarkers related to diabetes were determined. Results: Diabetic rats had a significantly decreased body weight, RBC-GHS, liver-GHS, and RBC-SOD activity and a significantly increased relative organ weight, blood glucose levels, insulin levels, insulin resistance, HbA1C, TC, TG, LDL, plasma-MDA, and liver-MDA when compared to the N-DW group. However, plant supplementation and metformin improved diabetes-related parameters, especially the combination of CME or FCME with SHE and metformin, which showed the greatest potential for improving diabetic conditions. (4) Conclusions: The research indicates that CME or FCME conjugated with SHE and metformin demonstrates the greatest potential for enhancing diabetic conditions, confirming positive synergism. These findings suggest that the combination of CME or FCME with SHE and metformin may be effective for diabetic treatment.